Diagnosing and Preventing Hearing Loss in the Genomic Age - McDermott, John H. (Trends Hear, 2019)
Over the past two decades, significant technological advances have facilitated the identification of hundreds of genes associated with hearing loss. Variants in many of these genes result in severe congenital hearing loss with profound implications for the affected individual and their family. This review collates these advances, summarizing the current state of genomic knowledge in childhood hearing loss. We consider how current and emerging genetic technologies have the potential to alter our approach to the management and diagnosis of hearing loss. We review approaches being taken to ensure that these discoveries are used in clinical practice to detect genetic hearing loss as soon as possible to reduce unnecessary investigations, provide information about reproductive risks, and facilitate regular follow-up and early treatment. We also highlight how rapid sequencing technology has the potential to identify children susceptible to antibiotic-induced hearing loss and how this adverse reaction can be avoided.